Integrasi Ilmu dan Praktik dalam Manajemen Syariah - Jessika Gafur Lamba; Irwan Misbach; Okta Nofri (Journal of Islamic Economic Studies, 2025)
This paper examines the intersection between the philosophy of science (epistemology, methodology, and ontology) and the development of Islamic management theory and practice. Using a critical literature review (library research), the study explores how Islamic epistemological foundations — including revealed sources and rational inquiry — shape paradigms, methods, and objectives in Islamic management (manajemen syariah). The review finds that integrating philosophy of science with maqāṣid al-sharīʿah and Islamic epistemology fosters a management model that pursues not only economic efficiency but also social welfare, justice, and ethical accountability. Recommendations include developing multi-method research approaches (hermeneutic-theoretical combined with empirical methods), embedding shariah values into performance metrics, and involving religious scholars in organizational policy design. Theoretical and practical implications for scholars, policymakers, and Islamic organizational.